Congress volume Munich 2013 - Maier, Christl M., 1962- (Vetus Testamentum, Supplements, 2014)
This volume presents the main lectures of the 21st Congress of the International Organization for the Study of the Old Testament (IOSOT) held in Munich, Germany, in August 2013. Seventeen internationally distinguished scholars present their current research on the Hebrew Bible, including the literary history of the Hebrew text, its Greek translation and history of interpretation. Some focus on archeological sources and the reconstruction of ancient Israelite religion while others discuss the formation of the biblical text and its impact for cultural memory. The volume gives readers a representative view of the most recent developments in the study of the Old Testament. Contributors are: Olivier Artus, Ehud Ben Zvi, Beate Ego, Irmtraud Fischer, Christian Frevel, Shimon Gesundheit, Timothy P. Harrison, Louis C. Jonker, James L. Kugel, Christoph Levin, Amihai Mazar, Steven L. McKenzie, Konrad Schmid, Yvonne Sherwood, Zipora Talshir, Akio Tsukimoto, and Jacques Vermeylen.